2019
DOI: 10.12659/msm.916305
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional Injection of Botulinum Toxin Type A Compared with Intralesional Injection of Corticosteroid for the Treatment of Hypertrophic Scar and Keloid: A Systematic Review and Meta-Analysis

Abstract: Background The optimal treatment for hypertrophic scar and keloid remains controversial. Therefore, the aim of this systematic review and meta-analysis was to compare the effectiveness of intralesional injection of botulinum toxin type A compared with placebo and intralesional injection of corticosteroid compared with placebo in patients with hypertrophic scar and keloid. Material/Methods Six databases were searched using Medical Subject Headings (MeSH) keywords and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 38 publications
6
45
0
8
Order By: Relevance
“…Apart from blocking acetylcholine release, BTX has antiinflammatory effects on wound healing and scar formation (57,58). A meta-analysis evaluating intralesional injection of BTX A versus corticosteroids and placebo in the treatment of hypertrophic scar and keloid showed that BTX A was more effective than the others (59). Another study conducted by An et al compared the effects of inflammation intervention in earlier phases (operationday) with that in later phase (2-week postoperative) on scar formation after thyroidectomy (60).…”
Section: Other Medicines Having Anti-scar Functionsmentioning
confidence: 99%
“…Apart from blocking acetylcholine release, BTX has antiinflammatory effects on wound healing and scar formation (57,58). A meta-analysis evaluating intralesional injection of BTX A versus corticosteroids and placebo in the treatment of hypertrophic scar and keloid showed that BTX A was more effective than the others (59). Another study conducted by An et al compared the effects of inflammation intervention in earlier phases (operationday) with that in later phase (2-week postoperative) on scar formation after thyroidectomy (60).…”
Section: Other Medicines Having Anti-scar Functionsmentioning
confidence: 99%
“…Data has been mixed, however, as to how botulinum toxin compares to steroid injections. While studies such as those by Shaarawy et al and Rasaii et al found no difference between the two treatments, Pruksapong et al found steroids to be superior, while a metanalysis performed by Bi et al showed botulinum toxin as superior [ 23 26 ]. Factors such as decreased adverse effects and greater improvement in symptoms offer additional benefits of botulinum toxin in comparison to triamcinolone [ 23 , 24 ].…”
Section: Injectionsmentioning
confidence: 99%
“…To date, various methods including intralesional therapies (corticosteroids, 5-fluorouracil, interferon, bleomycin injection, intralesional brachytherapy, intralesional botox), surgical excision, topical corticosteroid injection, radiation therapy (external beam radiotherapy; EBRT and brachytherapy), silicone gel therapies, compression therapy, and laser therapies have been trialled for the treatment of keloids. [5][6][7][8] Of these, intralesional corticosteroid injection, topical corticosteroid injection, surgical excision, and silicone gel therapies were reported to be successful for the treatment of penile keloids.…”
Section: Discussionmentioning
confidence: 99%